Pemahaman Agama dan Sikap Money Politic Siswa di MA Matholi’ul Huda - Jukari, Ahmad; Mardliyah, Laili; Sari, Cindy Prasiska; Robiyatie, Revianie Nor (AL-BURHAN, 2024)
This study was motivated by the large spotlight on money politics behavior in Madrasah for students who already have the right to vote. This study aims to obtain information related to religious understanding with students' attitudes towards the phenomenon of money politics ahead of the election. The study was conducted at Madrasah Aliyah Matholi'ul Huda Sokopuluhan Village with a sample of 73 students. The type of research is quantitative with survey research using a closed questionnaire as a data collection method. The results of the study indicate that the level of normative understanding of students that money politics is prohibited by religion and laws is very high. However, the understanding of some students that money politics is prohibited by religion and laws becomes biased when they see the practice of money politics in the field. some of those who consider money politics to be prohibited even consider giving money in elections as gossip or charity. The percentage of religious understanding with students' money politics attitudes shows that religiously, money politics is prohibited by religion (91.8%). The students' responses related to money politics based on statutory regulations showed that 65 students or 89.0% knew that money politics was prohibited in statutory regulations and only 8 students or 11.0% stated that they did not know that money politics was prohibited in statutory regulations.Keywords: understanding of religion, student behavior, money politics